2023
DOI: 10.1186/s12906-023-03851-x
|View full text |Cite
|
Sign up to set email alerts
|

Total flavonoids of Chrysanthemum indicum L inhibit acute pancreatitis through suppressing apoptosis and inflammation

Abstract: Acute pancreatitis (AP) is one of the most common acute abdomen. Inflammation and apoptosis are closely linked with AP development. Total flavonoids of Chrysanthemum indicum L (TFC) has been proved to inhibit inflammation and apoptosis. If TFC could suppress AP remains unclear. AP animal and cell models were established with Cerulein. The pancreatic tissue injury was measured with HE staining. Inflammatory factors were detected with ELISA method. The protein expression was evaluated with Western blotting. Inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Currently, drugs specific to AP are lacking, and most available treatments focus on symptom relief and supportive care (26). TCM is a highly effective method for treating AP due to its various benefits, including its ability to target multiple areas and its minimal adverse reactions (28,29). Previous animal and clinical experiments have confirmed the therapeutic impact of CH on AP, yet the precise molecular mechanisms behind it remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, drugs specific to AP are lacking, and most available treatments focus on symptom relief and supportive care (26). TCM is a highly effective method for treating AP due to its various benefits, including its ability to target multiple areas and its minimal adverse reactions (28,29). Previous animal and clinical experiments have confirmed the therapeutic impact of CH on AP, yet the precise molecular mechanisms behind it remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…IL6, when bound to its receptor, can initiate a cascade through JAK activation, and activated JAK kinase phosphorylates STAT3, inducing dimerization, leading to in ammation [43]. TNFA can activate NFKB, further causing a magni ed in ammatory reaction [44]. During an immune response, activated CD4 + and CD8 + T lymphocytes secrete large quantities of IL2.…”
Section: Discussionmentioning
confidence: 99%
“…Chrysanthemum indicum Linnén (C. indicum) is a medicinal and food herb, which is readily available in East Asia (22). Previous studies have reported that C. indicum may have antihypertensive, antioxidant, antiseptic and anticancer properties, as well as inhibiting lipogenesis (22)(23)(24)(25). Supercritical carbon dioxide fluid extraction has been successfully employed for the extraction process of flowers and buds of C. indicum because it can ensure a high extraction rate and the structural integrity of its volatile compounds, such as monoterpenes, sesquiterpenes and alkenes (26).…”
Section: Prevention Of Supercritical Carbon Dioxide Fluid Extract Fro...mentioning
confidence: 99%